Layanan Bimbingan Kelompok untuk Meningkatkan Pemahaman Diri Siswa Kelas XI SMAN 15 Medan dengan Penggunaan Media Ular Tangga - Dalimunthe, Deby Elystiadi; Khairina Ulfa Syaimi; Lailan Syafira Putri Lubis; Lilis Granella Sidabutar (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
This study aims to determine the effectiveness of group guidance services with snakes and ladders game media in improving self-understanding of class XI students of SMA Negeri 15 Medan. The background of this study is the low level of students' self-understanding which has an impact on lack of self-confidence, difficulty in recognizing potential and weaknesses, and doubt in making decisions. This study uses the Guidance and Counseling Action Research (PTBK) method which is implemented in two service cycles. The subjects of the study were seven class XI students who were selected based on the results of the AUM-Umum which showed that they had problems related to low self-understanding. Data collection techniques used questionnaires, observations, interviews, and documentation. The results showed a significant increase in the level of students' self-understanding. The average pre-cycle score of 47 (low category) increased to 67.1 (moderate category) after cycle I, and reached 85.7 (high category) at the end of cycle II. In addition, students showed positive behavioral changes such as increased self-confidence, the ability to identify strengths and weaknesses, and activeness in learning and social activities. The use of snakes and ladders games has been proven to be able to create a more relaxed and interactive learning atmosphere, making it easier for students in the process of self-reflection. Thus, group guidance services based on educational games can be an innovative alternative to improve students' self-understanding.